FORMATION OF PROFESSIONAL ORIENTATION OF FUTURE PSYCHOLOGISTS IN THE PROCESS OF POSTGRADUATE TRAINING (Pedagogy of Higher and Secondary Education, 2022)
The article analyzes theoretical and methodological principles of forming professional orientation of psychologists in the process of professional raining in universities. Identified the theoretical basis of research quality of future development of appropriate specialists in psychology.
Keywords: profession psychology; professional orientation; graduate retraining